A Study on the Effectiveness of Experiential Teaching in Mental Health Education Courses in Higher Education - Zhang, Bo; Abdullah, Azizah binti (Technium Social Sciences Journal, 2024)
Experiential teaching, as an innovative instructional model, emphasizes the creation of authentic or simulated scenarios within the learning process, allowing students to gain insight and understanding of course content through direct experiences. This approach enables students to better comprehend and retain knowledge of mental health, enhancing their psychological resilience and self-regulation abilities. In this study, two freshman classes, with comparable pre-test results in psychological resilience, were selected as the subjects. The experimental group received a combination of experiential and lecture-based teaching, while the control group was taught solely through lectures. This research aims to explore the impact of experiential teaching in mental health courses on students’ psychological resilience, ultimately contributing to improved quality and effectiveness of mental health education in higher education.